Analysis of the Effect of Abrasive Material and Polyurethane Coating Thickness Variations on ASTM A36 Steel Towards Corrosion Rate in Sea Water Environment - Herman Pratikno; Wimala Lalitya Dhanista; Felita Widya Hapsari (International Journal of Offshore and Coastal Engineering, 2021)
An unavoidable phenomenon of using steel as the main material in offshore structures and floating vessels is corrosion. One method of preventing corrosion is by coating and using polyurethane is one type of coating that is currently being developed in the maritime industry. But the success of this coating process is very dependent on the surface preparation process. The usual method used is blasting using an abrasive material. This study aims to find the response to the corrosion rate of polyurethane coating with thickness variations of 60 µm, 80 µm, and 100 µm by first blasting using abrasive material variations in the form of silica sand and steel grit. The result of the corrosion rate test showed that the lowest corrosion rate value was obtained in the variation of abrasive material in the form of steel grit. with a 100. µm of polyurethane coating thickness, that is 0,00008 mm/a. While the highest corrosion rate value was obtained in the variation of abrasive material in the form of silica sand with a 60 µm of polyurethane coating thickness, that is 0,02202 mm/a.